The study of creating of the awareness about substance addiction through contextbased learning - Özay Köse, Esra; Gül, Şeyda; Keskin, Bülent (Journal of Dependence, 2016)
Objective: The aim of this study is to create awareness about substance addiction for secondary school students. For this aim, it was examined the difference between awareness levels about substance addiction of the students who attended the course prepared with context-based learning and the students who attended to the course with traditional method. It was also assessed the status of the students’ awareness scores in terms of gender and grade. Method: The study was carried out with total of 229 students who attended 9-12th grade from secondary school in Erzincan. In the study, it was used quasiexperimental research design, the data collection tool was Substance Addiction Awareness Scale (SAAS) developed by the researchers. The data were analyzed with mean score, standard deviation, independent sample t test and one way ANOVA. Results: The findings indicated that there was a significant difference between the awareness levels of the students in experimental and control group in favor of experimental group. And also, there was no difference between the awareness levels of the students in terms of gender and grade. Conclusions: The findings indicated that context based learning approach affected positively the students’ awareness levels without gender and grade differences.